Effects of Some H1-Antagonists on the Sleep-Wake Cycle in Sleep-Disturbed Rats - Shin Tokunaga; Yasuhiro Takeda; Kazuaki Shinomiya; Masahiro Hirase; Chiaki Kamei (Elsevier, 2007)
The present study was undertaken to investigate the effects of some H1-antagonists on the sleep-wake cycle in sleep-disturbed rats in comparison with those of nitrazepam. Electrodes were chronically implanted into the frontal cortex and the dorsal neck muscle of rats for the electroencephalogram (EEG) and electromyogram (EMG), respectively. EEG and EMG were recorded with an electroencephalograph. SleepSign ver. 2.0 was used for EEG and EMG analysis. The total times of waking, non-rapid eye movement (non-REM), and rapid eye movement (REM) sleep were measured from 10:00 to 16:00. Nitrazepam showed a significant decrease in sleep latency, total waking time, and delta activity and an increase in the total non-REM sleep time. A significant decrease in the sleep latency was observed with diphenhydramine, chlorpheniramine, and cyproheptadine. Cyproheptadine also caused a significant decrease in the total waking time and increases in total non-REM sleep time, REM sleep time, slow wave sleep, and delta activity, although no remarkable effects were observed with diphenhydramine and chlorpheniramine. In conclusion, cyproheptadine can be useful as a hypnotic, having not only sleep inducing-effects, but also sleep quantity- and quality-increasing effects. Keywords:: sleep-disturbed rat, H1-antagonist, benzodiazepine hypnotic, sleep-wake cycle, delta activity